Design, development, and flight testing of a high endurance micro quadrotor helicopter. Issue 3 (September 2016) - Winslow, Justin; Benedict, Moble; Hrishikeshavan, Vikram; Chopra, Inderjit
This paper describes the experimental design studies conducted to maximize the hover endurance of a micro air vehicle-scale quadrotor helicopter (gross weight < 50 g) by careful design and selection of the individual subsystems while understanding their interdependencies. The different subsystems of the quadrotor that were examined include the rotors, motors, electronic speed controllers, gear transmission systems, battery, and airframe structure. An optimized micro air vehicle-scale rotor with a diameter of 110 mm and a figure of merit of 0.67 served as the basis for the vehicle design. Brushed and brushless motor systems were paired with the optimized rotor and were examined for maximum system level efficiency and capability to produce the required thrust. Propulsion systems using brushed motors with speed controllers and the optimum gear ratio showed up to 35% improvement in efficiency over brushless outrunner motors with speed controllers. Lithium-ion polymer batteries were compared and evaluated on voltage drop-off characteristics and achievable endurance versus weight. Quadrotor airframe weight has been minimized to 7.4% of the gross weight, representing a 30–50% decrease compared existing similarly sized quadrotors. The highest endurance was obtained using brushed motors with a 5.33:1 gear ratio and a 650 mAh battery. Presently, the longest continuous hover endurance achieved with this design is 31 min.